2020
DOI: 10.1080/20426445.2020.1861733
|View full text |Cite
|
Sign up to set email alerts
|

Within-tree and radial variations of wood properties in naturally regenerated trees of Betula platyphylla grown in Nikko, Japan

Abstract: Wood properties were investigated for nine naturally regenerated trees of Betula platyphylla Sukaczev var. japonica (Miq.) H. Hara in Nikko, Japan to effectively utilise the wood resources. The following properties were determined: stress-wave velocity of stems in radial direction, cell length, basic density, shrinkage, dynamic Young's modulus, modulus of elasticity, modulus of rupture, absorbed energy in impact bending, and compressive strength parallel to grain. All examined wood properties increased from pi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 30 publications
(98 reference statements)
7
7
0
Order By: Relevance
“…japonica (Miq.) H. Hara naturally grown in Japan, we recently reported that the boundary determined by radial variations of fiber length was around 1.5 to 4.2 cm from the pith or the 10th to 17th annual ring from the pith [9]. Similar results in terms of radial variations of the density and mechanical properties have been obtained in other Betula species (e.g., B. ermanii Cham., B. maximowicziana Regel, B. pendula Roth, and B. platyphylla), where the region around 5 to 8 cm from the pith has been clearly marked as a low-density and low-strength properties region [16][17][18].…”
Section: Introductionsupporting
confidence: 77%
See 4 more Smart Citations
“…japonica (Miq.) H. Hara naturally grown in Japan, we recently reported that the boundary determined by radial variations of fiber length was around 1.5 to 4.2 cm from the pith or the 10th to 17th annual ring from the pith [9]. Similar results in terms of radial variations of the density and mechanical properties have been obtained in other Betula species (e.g., B. ermanii Cham., B. maximowicziana Regel, B. pendula Roth, and B. platyphylla), where the region around 5 to 8 cm from the pith has been clearly marked as a low-density and low-strength properties region [16][17][18].…”
Section: Introductionsupporting
confidence: 77%
“…Similar results in terms of radial variations of the density and mechanical properties have been obtained in other Betula species (e.g., B. ermanii Cham., B. maximowicziana Regel, B. pendula Roth, and B. platyphylla), where the region around 5 to 8 cm from the pith has been clearly marked as a low-density and low-strength properties region [16][17][18]. These radial variations of wood properties might be related to the xylem maturation process [9,[11][12][13][14][15]18]. Therefore, further research is needed to clarify the xylem maturation process for B. platyphylla trees grown in Mongolia to understand the core wood and outer wood properties.…”
Section: Introductionmentioning
confidence: 96%
See 3 more Smart Citations